Assessment of IL-6 in the Oral Mucosal Healing with PerioKIN Hyaluronic 1%®and OzOHEAL-M ® in Rabbits - Mohanned Y Hamid; Ziad Hazim Deleme; Ahmed S Khudhur (University of Mosul, College of Dentistry, 2023)
Aims: To compare the effects of Hyaluronic acid (PerioKIN Hyaluronic 1%)® and ozonated oil (O3OHEAL-M) ® on healing after induced wounds in rabbits oral mucosa and to detect the presence of interleukin-6 (IL-6) as a biomarker using immunohistochemistry. Materials and methods: The study was conducted on (12) male New Zealand rabbits, randomly divided into two groups (6 animals per group) according to the healing periods (3rd,7th, and 14th) days. Two incisions were made on the buccal mucosa of each rabbit bilaterally. For the first group, the defects were filled with (PerioKIN Hyaluronic 1%) gel, (O3OHEAL-M) gel was applied for the second group, applied three times daily, two rabbits were randomly selected of each group at the (3rd, 7th, and 14th) days, and biopsies were taken. The biopsy specimens were subjected to Immunohistochemical evaluation to assess wound healing potential utilizing IL-6 as a marker. Results: Median scores of IL-6 expression for oral mucosa showed that at day three perioKIN group showed higher expression of the marker but at day seven there was equal and finally at day fourteen there is no expression of IL-6 marker in Ozoheal group, there was a statistically significant difference at all periods for Ozoheal group which means that Ozoheal has less reaction to local tissue response. Conclusion: Ozoheal drug is better than perioKIN gel as an anti-inflammatory action and thus could reduce the sequelae related to the inflammatory process.